EZH2 and CD79B mutational status over time in B‐cell non‐Hodgkin lymphomas detected by high‐throughput sequencing using minimal samples. Issue 7 (29th January 2013) - Saieg, Mauro Ajaj; Geddie, William R.; Boerner, Scott L.; Bailey, Denis; Crump, Michael; da Cunha Santos, Gilda
<x xml:space="preserve">Abstract</x> BACKGROUND Numerous genomic abnormalities in B‐cell non‐Hodgkin lymphomas (NHLs) have been revealed by novel high‐throughput technologies, including recurrent mutations in EZH2 (enhancer of zeste homolog 2) and CD79B (B cell antigen receptor complex‐associated protein beta chain) genes. This study sought to determine the evolution of the mutational status of EZH2 and CD79B over time in different samples from the same patient in a cohort of B‐cell NHLs, through use of a customized multiplex mutation assay. METHODS DNA that was extracted from cytological material stored on FTA cards as well as from additional specimens, including archived frozen and formalin‐fixed histological specimens, archived stained smears, and cytospin preparations, were submitted to a multiplex mutation assay specifically designed for the detection of point mutations involving EZH2 and CD79B, using MassARRAY spectrometry followed by Sanger sequencing. RESULTS All 121 samples from 80 B‐cell NHL cases were successfully analyzed. Mutations in EZH2 (Y646) and CD79B (Y196) were detected in 13.2% and 8% of the samples, respectively, almost exclusively in follicular lymphomas and diffuse large B‐cell lymphomas. In one‐third of the positive cases, a wild type was detected in a different sample from the same patient during follow‐up. CONCLUSIONS Testing multiple minimal tissue samples using a high‐throughput multiplex platform exponentially increases tissue availability for molecular analysis and might facilitate future studies of tumor progression and the related molecular events. Mutational status of EZH2 and CD79B may vary in B‐cell NHL samples over time and support the concept that individualized therapy should be based on molecular findings at the time of treatment, rather than on results obtained from previous specimens. Cancer (Cancer Cytopathol) 2013;121:377–386. © 2013 American Cancer Society.